DESIGN AND FABRICATION OF DECORATIVE LAWN MOWER AND MULTIPURPOSE AGRICUTTER MACHINE - NILESH S. JADHAV; SHUBHAM B. GORE; LAXMAN D. KUNCHALWAR (International Journal of Innovations in Engineering Research and Technology, 2021)
It is proposed to develop a multipurpose agricutter machine and decorative lawn mover to perform various operations in lawns to decorate it. The design is such that it reducescost and humanefforts and performstree operations in one set.The oscillating motion is given to cutter by cam follower arrangement to increase the cutting areaof cutter.The cutter setup is flexible such it can place on handle by spherical joint and use as hedge cutter. It can also place in vertical direction to cut the feed of animals. These three operationsperform on one machine which reduce requirement of indivisual machine for each operation.Senser is use to avoid damage to cutter by stones or any substance.This machine is useful for domestic purpose as there is no need to purchace uneconomical machines. It is eas to handle and use and compact in size with high efficiency